Out-of-school suspensions in U.S. public schools: relations with chronic teacher absenteeism - Fabes, Richard A.; O'Rourke, Holly; Catherine, Evandra; Shen, Zuchao; McDonald, Ashley (Frontiers in Developmental Psychology, 2023)
Out-of-school suspensions (OSSs) put students at risk for an array of negative social and academic outcomes. The rates of the use of OSS vary considerably from one school to another; however, school-level characteristics have not been studied extensively. The purpose of this study was to examine the degree to which chronic teacher absenteeism predicted the overall rates of OSS, as well as racial/ethnic disparities in its use. Although research has established that teachers are one of the most significant school-based factors affecting student success and learning, they need to be present in the classroom for students to derive these benefits. Using a national sample of public schools in the United States, the study's findings confirmed that schools with higher rates of chronic teacher absenteeism also had higher rates of the use of suspension. Moreover, within a school, higher proportions of chronic teacher absence were related to greater disparities in the rates of suspensions for Black students relative to white students. It was concluded that chronic absenteeism represents a significant risk factor that is related to the use of OSS with students in a school.